2022
DOI: 10.1002/acm2.13703
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an integrated whiteboard system on physics QA turnaround time

Abstract: Purpose To evaluate the impact of a digital whiteboard system integrated with data from the oncology information system (OIS) on the urgency of physics quality assurance (QA) tasks in the radiation oncology department. Methods Quality check list (QCL) items in the Mosaiq OIS corresponding to eight discrete, sequential steps in the treatment planning process were created. A whiteboard to graphically display active QCLs automatically and in real time was implemented in March 2020 using R shiny. QCL data with com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…To this end, several in‐house tracking systems or “whiteboards” have been developed and explored. These whiteboards allow users to visually track a patient's progress through the various stages of the planning process in real‐time and allow for real‐time updates on the planning status 6–9 . Gates and colleagues found that implementing a whiteboard reduced the proportion of needed next‐day physics Quality Assurance (QA)s by 27% 7 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, several in‐house tracking systems or “whiteboards” have been developed and explored. These whiteboards allow users to visually track a patient's progress through the various stages of the planning process in real‐time and allow for real‐time updates on the planning status 6–9 . Gates and colleagues found that implementing a whiteboard reduced the proportion of needed next‐day physics Quality Assurance (QA)s by 27% 7 .…”
Section: Introductionmentioning
confidence: 99%
“…These whiteboards allow users to visually track a patient's progress through the various stages of the planning process in real‐time and allow for real‐time updates on the planning status. 6 , 7 , 8 , 9 Gates and colleagues found that implementing a whiteboard reduced the proportion of needed next‐day physics Quality Assurance (QA)s by 27%. 7 A custom electronic workflow management program was created and implemented by Medlever, Inc. Shailja and colleagues found that the program is effective in presenting supporting descriptive data across facility lines and multiple process steps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation